EPIGENETIC INFLUENCES EARLY IN LIFE: NUTRITIONAL AND STRESS FACTORS. (July 2016) - Pot, B.
Abstract : While recent research shows the importance of the microbiota in e.g. the development of the immune system, it also became evident that the very early phases in life, even before birth, may be crucial. Later in life the impact of microbiota interventions may be less effective. While we don't know at this stage how and where and when the microbiota can change the human DNA, we can learn from epigenetic observational studies linked to e.g. malnutrition (the Dutch famine study) or linked to other types of stress (the Canadian ice storm babies). Whether these observations can be extrapolated to, or even explained by 'microbiota stresses', remains to be clarified.